Comparative study of optical and luminescence properties of Sm3+-ions doped Li2O–Gd2O3–PbO–SiO2 and Li2O-GdF3-PbO–SiO2 glasses for orange emission solid state device application - I. Khan (2020)
© 2020 Elsevier B.V. 25Li2O–05Gd2O3– 15PbO – (55-x) SiO2:x Sm2O3 (LPOSm) and 25Li2O–05GdF3- 15PbO – (55-x) SiO2:x Sm2O3 (LPFSm)glasses were prepared by melt quenching method. Optical, luminescence JO-parameters and radiative properties were studied using various techniques. While comparing Ω2 parameter values between LPOSm05 and LPFSm05, the LPFSm05 glass has more asymmetric environment around Sm3+-ions and more covalency between Sm3+-O bonding then LPOSm05 glass. Moreover, LPFSm05 has higher value of branching ratio than LPOSm05 showing its suitability for laser active medium. The current investigation reveals that value of IR/O-ratio for LPFSm05 is more than LPOSm05 showing its more asymmetric nature and more local disorder for Sm3+-ions than LPOSm05 glass. From evaluated results the CIE-color-coordinates for LPOSm and LPFSm glasses fall in orange region. The calculated value of prepared LPOSm and LPFSm glass are less than warm CCT (<4000 K). The lifetime of 4G5/2state atλext = 402 nm and λemi = 600 nm for LPOSm glasses is longer than LPFSm glasses. The dominant interaction responsible for non-exponential behavior for higher concentration in present glasses were found to be dipole-dipole type of interaction for energy transfer between donor (Sm3+) and acceptor (Sm3+) ions. From the present investigation it is suggested that presents glasses are suitable for orange light emitting devices (LEDs and laser).